Local Macrophage-Related Immune Response Is Involved in Cochlear Epithelial Damage in Distinct Gjb2-Related Hereditary Deafness Models - Xu, Kai; Chen, Sen; Xie, Le; Qiu, Yue; Bai, Xue; Liu, Xiao-Zhou; Zhang, Hui-Min; Wang, Xiao-Hui; Jin, Yuan; Sun, Yu; Kong, Wei-Jia (Frontiers in Cell and Developmental Biology, 2021)
The macrophage-related immune response is an important component of the cochlear response to different exogenous stresses, including noise, ototoxic antibiotics, toxins, or viral infection. However, the role of the immune response in hereditary deafness caused by genetic mutations is rarely explored. GJB2, encoding connexin 26 (Cx26), is the most common deafness gene of hereditary deafness. In this study, two distinct Cx26-null mouse models were established to investigate the types and underlying mechanisms of immune responses. In a systemic Cx26-null model, macrophage recruitment was observed, associated with extensive cell degeneration of the cochlear epithelium. In a targeted-cell Cx26-null model, knockout of Cx26 was restricted to specific supporting cells (SCs), which led to preferential loss of local outer hair cells (OHCs). This local OHC loss can also induce a macrophage-related immune response. Common inflammatory factors, including TNF-α, IL-1β, Icam-1, Mif, Cx3cr1, Tlr4, Ccl2, and Ccr2, did not change significantly, while mRNA of Cx3cl1 was upregulated. Quantitative immunofluorescence showed that the protein expression of CX3CL1 in Deiters cells, a type of SC coupled with OHCs, increased significantly after OHC death. OHC loss caused the secondary death of spiral ganglion neurons (SGNs), while the remaining SGNs expressed high levels of CX3CL1 with infiltrated macrophages. Taken together, our results indicate that CX3CL1 signaling regulates macrophage recruitment and that enhancement of macrophage antigen-presenting function is associated with cell degeneration in Cx26-null mice.